PERANCANGAN FILM DOKUMENTER MAKNA DAN NILAI DALAM TRADISI SAPARAN (Studi Kasus Kelurahan Tegalrejo Salatiga) - Anthony Y.M. Tumimomor; Heri Mahardika (TANRA: Jurnal Desain Komunikasi Visual Fakultas Seni dan Desain Universitas Negeri Makassar, 2018)
Salatiga is a city located in Central Java Province where the community consists of various tribes, different backgrounds, and beliefs. Salatiga has a tradition of Saparan, there are some areas that still adhere to the tradition of Saparan as a legacy of elderly. Saparan di Tegalrejo is held every once a year in a Sapar month that is identical with village Merti activities or maintaining the village. Each tradition procession has its own meaning and values that are used as a guideline for society. By using a qualitative approach and linear strategy, a documentary media is produced that can visualize the meaning and value in the existing Saparan tradition in Tegalrejo Salatiga village to the audience.